Removal of levofloxacin from aqueous solution by green synthesized magnetite (Fe3O4) nanoparticles using Moringa olifera: Kinetics and reaction mechanism analysis - Altaf, Sikandar; Zafar, Rabeea; Zaman, Waqas Qamar; Ahmad, Shakil; Yaqoob, Khurram; Syed, Asad; Khan, Asim Jahangir; Bilal, Muhammad; Arshad, Muhammad (Ecotoxicology and environmental safety, 2021)
Levofloxacin antibiotic is frequently being detected in the environment and regarded as an emerging contaminant. The present study was focused on the green synthesis of magnetite (Fe3O4 – gINPs) nanoparticles from Moringa olifera and its efficiency for removal of levofloxacin from aqueous solution. The adsorbent magnetite nanoparticles (Fe3O4) were prepared by green synthesis using Moringa olifera and coprecipitation method. Characterizations analyses of both chemically and green synthesized nanoparticles were performed by SEM, XRD, and FTIR. The average crystallite size of gINPs was 14.34 nm and chemically synthesized was 18.93 nm. The performance of the synthesized product was evaluated by adsorption capacity and removal efficiency. The parameters considered included adsorbent (gINPs) dosage, initial concentration of adsorbate, pH, contact time, and temperature. The obtained data were fitted to kinetic and isotherm models to determine the mechanism. Adsorption batch experiments were conducted to determine the reaction mechanism by studying kinetics while fitting isotherm models for samples analyzed using HPLC at 280 nm. Results showed that 86.15% removal efficiency of 4 mg L-1 levofloxacin was achieved by 100 mg L-1 gINPs in 24 h contact time when all other parameters (pH 7, temperature 25 °C) were kept constant. The maximum adsorption capacity achieved at equilibrium was 22.47 mg/g. Further, it was identified as a pseudo-second-order model with R2 = 0.965 for adsorption kinetics while isotherm data better fitted to the Freundlich model compared to Langmuir isotherm with R2 = 0.994. The potential pathway determined for levofloxacin removal was chemisorption with minor diffusion, multilayer, spontaneous and exothermic processes on the gINPs (Fe3O4). Reusability experiments were conducted in four cycles and removal efficiency varied from 85.35% to 80.47%, indicating very high potential of the adsorbent for re-use. [Display omitted] •Green synthesis of magnetite nanoparticles using Moringa olifera was achieved.•Synthesized nanoparticles exhibited up to 86.15% removal efficiency of levofloxacin.•Maximum adsorption capacity of levofloxacin achieved at equilibrium was 22.47 mg/g.•Dominant mechanism for removal appeared as chemisorption.